Drug/polymer nanoparticles prepared using unique spray nozzles and recent progress of inhaled formulation - Tetsuya Ozeki; Tatsuaki Tagami (Elsevier, 2014)
Inhaled formulations are promising for pulmonary and systemic non-pulmonary diseases. Functional engineered particles including drugs and drug-loaded nanocarriers have been anticipated because they can improve drug delivery efficacy against target sites in the lungs or blood. In this review, unique spray nozzles (e.g., four-fluid spray nozzle and two-solution mixing type nozzle) for the preparation of nanocomposite particles which mean microparticles containing drug nanoparticles are described. These nozzles can produce nanocomposite particles in one-step and their spray drying system is suitable for scaling-up. Nanocomposite particles are useful in improving drug absorption and delivery efficacy against alveolar macrophages. In addition, recent studies on several pulmonary diseases (tuberculosis, lung cancer, cystic fibrosis, pneumonia, vaccine and others) and related inhaled formulations were also reviewed.